2015
DOI: 10.1016/j.proci.2014.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of porous walled tubes on detonation transmission into unconfined space

Abstract: Experiments were carried out to investigate the failure mechanisms in the critical tube diameter phenomenon for stable and unstable mixtures. It was previously postulated that in unstable mixtures where the detonation structure is highly irregular, the failure during the diffraction is caused by the suppression of the instability responsible for the generation of local explosion centers. In stable mixtures, typically with high argon dilution and where the detonation is characterized by very regular cell, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although these calculations are performed for a weakly stable detonation using simplified chemical kinetics, the re-initiation results show many similarities to those observed in the experimental work of Mehrjoo et al (2015). They used porous-walled tubes to suppress transverse instability and demonstrated that successful transmission was reliant on frontal instability.…”
Section: Effect Of the Reflected Rarefaction Wavementioning
confidence: 69%
“…Although these calculations are performed for a weakly stable detonation using simplified chemical kinetics, the re-initiation results show many similarities to those observed in the experimental work of Mehrjoo et al (2015). They used porous-walled tubes to suppress transverse instability and demonstrated that successful transmission was reliant on frontal instability.…”
Section: Effect Of the Reflected Rarefaction Wavementioning
confidence: 69%
“…The importance of cellular instabilities in the outcome of the detonation diffraction has been further elucidated by Mehrjoo et al 16,17 . Their studies show that, by generating artificially flow perturbations using small obstacles or by damping transverse waves using porous media at the tube exit, the transmission of a diffracting detonation wave can be promoted or suppressed, respectively.…”
Section: And Latermentioning
confidence: 99%
“…Experiments were recently conducted by Mehrjoo et al [16,17] to discriminate between the two modes of failure conjectured by Lee [11] and clarify the importance of instability on the critical tube phenomenon. Two series of experiments were conducted: one by generating artificially small flow instabilities using small obstacles with different blockage ratios placed at the tube exit and the other by damping transverse instability using porous media.…”
Section: Introductionmentioning
confidence: 99%